2020
DOI: 10.1371/journal.pone.0231201
|View full text |Cite
|
Sign up to set email alerts
|

Association between cigarette smoking and the risk of dysmenorrhea: A meta-analysis of observational studies

Abstract: BackgroundEmerging studies have found inconsistent results on the potential relationship between cigarette smoking and dysmenorrhea. Therefore, the aim of this study was to quantitatively synthesize the previous findings on the preceding relationship using meta-analysis. MethodsPrevious studies on the association between cigarette smoking and dysmenorrhea, published not later than November 2019, were systematically searched, using MeSH heading and/or relevant terms, in the electronic databases of PubMed, Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…Additionally, Parazzini et al 13 found that the relative risk of dysmenorrhea was increased by smoking and decreased among alcohol drinkers. In consistency with this result, a meta-analysis of observational study conducted by Qin et al 14 found a significant association between cigarette smoking (both current and former smoking) and dysmenorrhea. Another meta-analysis conducted by Jenabi et al 15 found a significant association between smoking and dysmenorrhea.…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, Parazzini et al 13 found that the relative risk of dysmenorrhea was increased by smoking and decreased among alcohol drinkers. In consistency with this result, a meta-analysis of observational study conducted by Qin et al 14 found a significant association between cigarette smoking (both current and former smoking) and dysmenorrhea. Another meta-analysis conducted by Jenabi et al 15 found a significant association between smoking and dysmenorrhea.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, smoking is considered a risk factor for PD. This is likely due to nicotine, which causes vasoconstriction, resulting in myometrial contraction and reduction in endometrial blood flow, which is common in dysmenorrhea [ 55 ]. An Australian cohort study, conducted on 9067 young females, who were followed between 2000 and 2012, found that smoking was significantly associated with menstrual pain (OR = 1.41), and more commonly attributed to initiation at an early age, below 15 years (OR = 1.50) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short sleeping hours and not having breakfast regularly were associated with moderate-to-severe dysmenorrhea in a previous study [ 8 ]. In addition, caffeine consumption [ 9 ], alcohol consumption, and smoking [ 10 ] were also associated with dysmenorrhea. Moreover, mental stress [ 11 , 12 , 13 ] and a lack of exercise [ 14 ] were related to the severity of dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%